PENGARUH DISIPLIN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DI PT JMS BATAM - HUTASOIT, ELI DIANA; simanjuntak, Jontro (LPPM Universitas Putera Batam, 2021)
This study aims to (1) find out whether there is an influence of discipline on employee performance at PT.JMS (2) find out whether there is an effect of training on employee performance at PT.JMS (3) find out whether there is an influence of discipline and training on employee performance at PT. JMS. This research is a quantitative research which is included in correlation research using survey method. Data was collected using a questionnaire distributed to 171 respondents. Analysis of the data using multiple linear regression test, t-test and F-test. The results of the analysis obtained (1) the influence of discipline on employee performance with a significance value of 0.003 <0.05. (2) there is an effect of training on employee performance with a significance value of 0.001 <0.05. (3) Discipline and training have a significant effect on employee performance with a value of F_count>F_table of 13.743> 3.05 and a significance value of 0.000 <0.05.